The impacts of commonly used medications on the trans-sulphuration pathway - Mansour Dakhilalla Alsaeedi, Asrar (2025)
Worldwide life expectancy is predicted to increase, which can lead to an increased reliance on medications to manage multimorbidity. Self-medication and cost of living crisis has increased this pattern. The trend towards increased medication use can increase the possibility of having a larger population at risk of micronutrient deficiencies / inadequacy in users. Despite the widespread use of medications, studies on drug-nutrient interactions remain limited. This is particularly concerning for critical metabolic processes like the trans-sulphuration pathway (TSP) that depend on vitamin B6 for its flux. This work employed a multi-faceted approach aimed at providing crucial insights into how commonly prescribed drugs influence the TSP.